Immune-mediated disease caused by climate change-associated environmental hazards: mitigation and adaptation - Agache, Ioana; Akdis, Cezmi; Akdis, Mubeccel; Al-Hemoud, Ali; Annesi-Maesano, Isabella; Balmes, John; Cecchi, Lorenzo; Damialis, Athanasios; Haahtela, Tari; Haber, Adam L.; Hart, Jaime E.; Jutel, Marek; et al. (Frontiers in Science, 2024)
Global warming and climate change have increased pollen burden and the frequency and intensity of wildfires, sand and dust storms, thunderstorms, and heatwaves – with concomitant increases in air pollution, heat stress, and flooding. These environmental stressors alter the human exposome and trigger complex immune responses. In parallel, pollutants, allergens, and other environmental factors increase the risks of skin and mucosal barrier disruption and microbial dysbiosis, while a loss of biodiversity and reduced exposure to microbial diversity impairs tolerogenic immune development. The resulting immune dysregulation is contributing to an increase in immune-mediated diseases such as asthma and other allergic diseases, autoimmune diseases, and cancer. It is now abundantly clear that multi-sectoral, multidisciplinary, and transborder efforts based on Planetary Health and One Health approaches (which consider the dependence of human health on the environment and natural ecosystems), are urgently needed to adapt to and mitigate the effects of climate change. Key actions include reducing emissions and improving air quality (through reduced fossil fuel use), providing safe housing (e.g., improving weatherization), improving diets (i.e., quality and diversity) and agricultural practices, increasing environmental biodiversity and green spaces. There is also a pressing need for collaborative, multidisciplinary research to better understand the pathophysiology of immune diseases in the context of climate change. New data science techniques, biomarkers, and economic models should be used to measure the impact of climate change on immune health and disease, to inform mitigation and adaptation efforts, and to evaluate their effectiveness. /.../